2010
DOI: 10.1684/agr.2010.0436
|View full text |Cite
|
Sign up to set email alerts
|

Diversités phénotypique et morphométrique des poulets locaux (Gallus gallus) de deux zones agroécologiques de Côte d'Ivoire*

Abstract: Diversité s phé notypique et morphomé trique des poulets locaux (Gallus gallus) de deux zones agroé cologiques de Cô te d'Ivoire* Ré sumé Avec comme objectif une meilleure gestion des ressources génétiques avicoles, une caractérisation phénotypique et morphométrique de l'espèce Gallus gallus domesticus a été entreprise dans deux zones agroécologiques (forêt et savane) de Côte d'Ivoire. Un échantillon de 439 poules et 193 coqs a été photographié, décrit et mesuré individuellement. Une grande variabilité phénoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The same goes for live weight and all biometric measurements which were in favor of males. This result is in agreement with those of other authors ( Yapi-Gnaore et al,2010 ; Adeoye et al,2017 ). Current data demonstrated that sex influenced most biometric characteristics of domestic geese.…”
Section: Discussionsupporting
confidence: 94%
“…The same goes for live weight and all biometric measurements which were in favor of males. This result is in agreement with those of other authors ( Yapi-Gnaore et al,2010 ; Adeoye et al,2017 ). Current data demonstrated that sex influenced most biometric characteristics of domestic geese.…”
Section: Discussionsupporting
confidence: 94%
“…This is the case of the yellow shank phenotype due to a recessive autosomal mutation at the W locus [ 50 ] found in all commercial layers, either white-egg or brown-egg, and in several broiler lines, whereas the wild type is a grey-blue shank colour. Previous surveys showed that the yellow shank phenotype is quite rare in Benin (5% [ 14 ]) and Côte d’Ivoire (15% [ 51 ]) or in other African countries such as Senegal (4% [ 52 ]), while it is much more common either in Cameroon (31 to 38% [ 53 , 54 ]) or Morocco (60% in the studied sample; Benabdeljelil, personal observation). Furthermore, the presence of the W mutation was found to be correlated with an improvement of anatomical traits in Cameroon [ 55 ].…”
Section: Discussionmentioning
confidence: 86%
“…Such preference has the effect that the sale price of local chickens (and eggs) is higher than that of products from commercial lines in African countries, including those studied here [ 49 , 56 - 59 , 62 , 63 ]. We also observed that phenotypic variability is very important due to the diversified social uses of local chickens [ 51 , 54 , 64 ] such as religious rituals or indigenous pharmacopeia. Some traits may be retained from industrial birds when they have a relative advantage, particularly the white color, as described by [ 6 ] who observed that a white plumage color was a peace symbol in Benin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional poultry farming in sub-Saharan Africa and more specifically in Togo, contributes to the strengthening of family farming through its contribution to the creation of jobs, incomes and the achievement of food security objectives for rural households [1][2][3] . In recent decades, with the rapid urbanization of rural areas, intensive poultry farming is developing.…”
Section: Introductionmentioning
confidence: 99%